The study of synaptic plasticity in the ZnO memristor elements for neuromorphic AI - R. V. Tominov; Z. E. Vakulov; D. S. J. Rodriguez; I. S. Ugryumov; V. A. Smirnov (Journal of Advanced Dielectrics)
The paper presents the results of experimental studies of synaptic plasticity in a memristive memory element based on nanocrystalline ZnO films grown by pulsed laser deposition. The obtained results can be used in the development of technological bases for the formation of high-performance multi-level artificial synapses for elements of neuroelectronics and hardware neural networks.